Luta pela terra no Território Prof. Cory/Andradina (SP): trajetória das famílias do Assentamento Santa Maria da Lagoa em Ilha Solteira-SP - Silva, Débora Pavani [UNESP]; Sant'ana, Antonio Lázaro [UNESP] (Universidade Estadual Paulista (UNESP), 2024)
The Território Prof. Cory/Andradina (SP), located in northwest São Paulo, has a high concentration of rural settlements, result of the expropriation of private lands due to a great pressure from social movements. The aim of this article is to analyze the trajectories of the struggle for land in the Território Prof. Cory/Andradina, focusing on the PA Santa Maria da Lagoa, located in the municipality of Ilha Solteira-SP. The research was carried out within the limits of the aforementioned Territory and the main source of information was the social actors who experienced the struggle through the qualitative methodology of Oral History. For that, 37 settled social actors who led or had active participation in the struggle processes were interviewed, four of them from the Santa Maria da Lagoa Settlement. The said Settlement was created in 2005, at the time with the highest intensity of occupations by social movements fighting for land in the Territory. In the case of Santa Maria da Lagoa, there was no occupation and there was no camp in the area, but the trajectories of the settled families allow us to observe the existence of a network of camps, consolidated at the beginning of this century, evidencing a long process of struggles.

El Territorio Prof. Cory/Andradina (SP), ubicada en el noroeste de São Paulo, tiene una alta concentración de asentamientos rurales, resultado de la expropiación de tierras privadas frente a una gran presión de los movimientos sociales. El objetivo de este artículo es analizar las trayectorias de la lucha por la tierra en el Territorio Prof. Cory/Andradina, con foco en el PA Santa Maria da Lagoa, ubicado en el municipio de Ilha Solteira-SP. La investigación se realizó dentro de los límites del mencionado Territorio y la principal fuente de información fueron los actores sociales que vivieron la lucha a través de la metodología cualitativa de la Historia Oral. Para eso, fueron entrevistados 37 actores sociales asentados que lideraron o tuvieron participación activa en los procesos de lucha, cuatro de ellos del Asentamiento Santa Maria da Lagoa. Dicho Asentamiento fue creado en el año 2005, momento de mayor intensidad de ocupaciones por movimientos sociales que luchan por la tierra en el Territorio. En el caso de Santa Maria da Lagoa, no hubo ocupación y no hubo campamento en la zona, pero las trayectorias de las familias asentadas permiten observar la existencia de una red de campamentos, consolidada a principios de este siglo, evidenciando un largo proceso de luchas.

O Território Prof. Cory/Andradina (SP), localizado no noroeste paulista, possui uma alta concentração de assentamentos rurais, resultado da desapropriação de terras particulares diante de grande pressão dos movimentos sociais. O objetivo deste artigo é analisar as trajetórias da luta pela terra no Território Prof. Cory/Andradina, com enfoque para o PA Santa Maria da Lagoa, localizado no município de Ilha Solteira-SP. A pesquisa foi realizada dentro dos limites do Território mencionado e a principal fonte de informações foram os atores sociais que vivenciaram a luta por meio da metodologia qualitativa da História Oral. Para tanto, foram entrevistados 37 atores sociais assentados que lideraram ou tiveram participação ativa nos processos de lutas, sendo quatro do Assentamento Santa Maria da Lagoa. O referido Assentamento foi criado em 2005, na época com maior intensidade de ocupações pelos movimentos sociais de luta pela terra no Território. No caso do Santa Maria da lagoa não ocorreu ocupação e nem havia acampamento na área, mas as trajetórias das famílias assentadas nos permitem observar a existência de uma rede de acampamentos, consolidada no início deste século, evidenciando um longo processo de lutas.
Struggle for land in Território Prof. Cory/Andradina (SP): trajectory of the families of the Santa Maria da Lagoa Settlement in Ilha Solteira-SP
Lucha por la tierra en Território Prof. Cory/Andradina (SP): trayectoria de las familias del Asentamiento Santa Maria da Lagoa en Ilha Solteira-SP
Keywords: Encampment; Landless Rural Workers Movement; sugar cane; public policy.; Acampamentos; Movimento dos Trabalhadores Rurais sem Terra; cana-de-açúcar; políticas públicas.